Bibliography of the works by Zbigniew Bela (1949–2018), a philologist, prosaist, and pharmacy historian - Michał Kokowski (Studia Historiae Scientiarum)
The bibliography presents the list of publications by Zbigniew Bela (1949–2018), a philologist, prosaist, and historian of pharmacy.